2008
DOI: 10.1097/pas.0b013e31817a9061
|View full text |Cite
|
Sign up to set email alerts
|

Solitary Peripheral Ciliated Glandular Papillomas of the Lung

Abstract: We report 3 cases of solitary papillomas located in peripheral regions of the lung that are extremely rare in the literature. The patients were 75-year-old and 72-year-old men and a 53-year-old woman. One patient complained of recurrent hemoptysis. The other 2 had no symptoms, but abnormal nodular shadows were revealed by chest radiographs during a health check. The maximum diameters of the tumors were 1.0, 1.4, and 1.1 cm, respectively. The 3 tumors gave almost the same histologic findings. Papillomatous fron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
44
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 49 publications
(47 citation statements)
references
References 11 publications
3
44
0
Order By: Relevance
“…The maximum value, 12.0%, was seen in the bronchiolar region of one case and the peripheral regions showed low values of 4.7%, 5.7%, and 2.3%, respectively [10]. The p53 labeling index was less than 10% in each of the three cases [10].…”
Section: Discussionmentioning
confidence: 87%
See 4 more Smart Citations
“…The maximum value, 12.0%, was seen in the bronchiolar region of one case and the peripheral regions showed low values of 4.7%, 5.7%, and 2.3%, respectively [10]. The p53 labeling index was less than 10% in each of the three cases [10].…”
Section: Discussionmentioning
confidence: 87%
“…Miyoshi et al [14] noted YUJM VOLUME 34, NUMBER 2, DECEMBER 2017 a small number of positive cells for p53 and Ki-67 were scattered in mixed squamous cell and glandular papilloma. Aida et al [10] reported the Ki-67 labeling index ranged from 2.3% to 12.0% in their three cases of glandular papilloma. The maximum value, 12.0%, was seen in the bronchiolar region of one case and the peripheral regions showed low values of 4.7%, 5.7%, and 2.3%, respectively [10].…”
Section: Discussionmentioning
confidence: 91%
See 3 more Smart Citations